THE INFLUENCE OF LEG MUSCLE STRENGTH, FLEXIBILITY AND ANKLE-FOOT COORDINATION ON THE PASSING ABILITY - Nasution, Harry Syahputra; Irawan, Roma; Akbar, Muh. Ali; Sulistianingsih, Annisa; Wenly, Ayu Purnama (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study aims to reveal the direct and indirect effects, as well as the simultaneous influence of exogenous variables on endogenous variables. This type of research is quantitative with a path analysis approach. Data were analyzed by path analysis through structural model testing at α = 0.05. The results showed that: 1) there was a direct effect of leg muscle strength on the passing ability of 9.61%, 2) there was a direct effect of flexibility on the passing ability of 8.41%, 3) there was a direct effect of ankle coordination on the passing ability amounted to 15.28%, 4) there is an indirect effect of leg muscle strength through ankle coordination on passing ability is 48.16%, 5) there is an indirect effect of flexibility through ankle coordination on passing ability is 44.35% , and 6) there is an effect of leg muscle strength, flexibility and ankle coordination on the passing ability of 67.50%. From the analysis of the direct and indirect effects, it is concluded that the big influence is the indirect variable of leg muscle strength through ankle coordination, which is 48.16%.